Examining equity and graduation rates at two institutions using a course deficit model and the collaborative learning through active sense-making in physics curriculum - Cassandra A. Paul; David J. Webb (Physical Review Physics Education Research)
We have previously described the reformed introductory physics course, collaborative learning through active sense-making in physics (CLASP), for bioscience students at a large public research one university (Original University) and presented evidence that the course was more successful and more equitable than the course it replaced by several measures. Now we compare the original success of CLASP with an implementation at a second institution. We find that the original results hold at another institution despite some changes to the original curriculum and a somewhat different student population. We find that students who take CLASP are (1) less likely to drop, (2) less likely to fail, and (3) do as well in later coursework when compared to students who took the courses that CLASP replaced, even if that coursework is not similarly reformed. We find the above items to be independently true for historically marginalized students and remarkably, also find that (4) marginalized students who take CLASP are more likely to graduate from a science, technology, engineering, and mathematics field. We use a course deficit model perspective to examine these results and discuss some of the factors that may have contributed to this success. We argue that higher education has the tools needed to significantly increase equity and improve student success and retention.